Homozygosity mapping of Portuguese and Japanese forms of ataxia-oculomotor apraxia to 9p13, and evidence for genetic heterogeneity. - Moreira, M. (2001)
Abstract Ataxia with oculomotor apraxia (AOA) is characterized by early-onset cerebellar ataxia, ocular apraxia, early areflexia, late peripheral neuropathy, slow progression, severe motor handicap, and absence of both telangiectasias and immunodeficiency. We studied 13 Portuguese families with AOA and found that the two largest families show linkage to 9p, with LOD scores of 4.13 and 3.82, respectively, at a recombination fraction of 0. These and three smaller families, all from northern Portugal, showed homozygosity and haplotype sharing over a 2-cM region on 9p13, demonstrating the existence of both a founding event and linkage to this locus, AOA1, in the five families. Three other families were excluded from this locus, demonstrating nonallelic heterogeneity in AOA. Early-onset cerebellar ataxia with hypoalbuminemia (EOCA-HA), so far described only in Japan, is characterized by marked cerebellar atrophy, peripheral neuropathy, mental retardation, and, occasionally, oculomotor apraxia. Two unrelated Japanese families with EOCA-HA were analyzed and appeared to show linkage to the AOA1 locus. Subsequently, hypoalbuminemia was found in all five Portuguese patients with AOA1 with a long disease duration, suggesting that AOA1 and EOCA-HA correspond to the same entity that accounts for a significant proportion of all recessive ataxias. The narrow localization of AOA1 should prompt the identification of the defective gene.